PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN REPUTASI PERUSAHAAN TERAHADAP MINAT MELAMAR KERJA GENERASI Z DI KABUPATEN BEKASI - Nur Romadhon, Setyo Wibowo; Khatimah, Husnul (Taksasila Edukasi Insani, 2025)
The purpose of this study is to examine the influence of corporate social responsibility and company reputation on the job application interest of Generation Z in Bekasi Regency. The population in this study consists of Generation Z individuals in Bekasi Regency. This study uses a quantitative descriptive method. Data were collected through online questionnaires distributed to a sample of 132 respondents selected using purposive sampling technique. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. Based on the data processing results using SmartPLS, the path coefficient for corporate social responsibility (X1) is 0.323 and for company reputation (X2) is 0.572 on job application interest (Y). The T-statistics values are 3.840 and 7.224 respectively, with p-values of 0.000, indicating that both variables have a positive and significant effect on the job application interest of Generation Z in Bekasi Regency. Keywords : Corporate Social Responsibility, Company Reputation, Interest in Applying For a Job.